Strategy for Reducing Stunting Rates in Mandalakasih Village, Pameungpeuk, Kab. Garut - Suwandi, Deden Winda; Putri Rachmaida, Nabila; Munawar, Azrina Rival; Kusuma, Erlang Darma; Kusuma, Rahiel Rindu; Dinata, Rizki Wangsa; Ibrahim, Maulana; Farida, Dida (Fakultas Kewirausahaan Universitas Garut, 2023)
Stunting is a serious problem in many countries, including Indonesia. In Mandalakasih Village, Pameungpeuk, Kab. Garut. The prevalence of stunting is still high, so it has become the village's main program in efforts to overcome health problems. Stunting is a chronic nutritional problem caused by a lack of nutritional intake over a long period of time, which can disrupt growth in children. Efforts to reduce the stunting rate in Mandalakasih Village were carried out through an understanding survey and direct education as an effort to prevent stunting. There were 285 correspondents for this research, consisting of 127 pregnant women and 158 parents with babies aged 0-23 months. The results of this research showed that there was an increase in insight into preventing stunting, namely for pregnant women it was 99.05%, while for parents with children aged 0-23 months it was 84.68%.